The story of this special issue on critical perspectives in work and organizational psychology. Issue 1 (5th December 2022) - Abrams, Ruth; Bal, P. Matthijs; D'Cruz, Premilla; Hornung, Severin; Islam, Gazi; McDonald, Matthew; Sanderson, Zoe; Tonelli, Maria José
Abstract: In this editorial, we tell the story of how the Special Issue on Critical Perspectives in Work and Organizational Psychology (CWOP) came about, how it fits within the broader agenda of building a critical community within Work and Organizational Psychology, and how future research and thought may be inspired by the collection of critical papers related to work and organizational psychology. We introduce the term "criticalizing" as a key concept in how the Special Issue was developed by the editorial team and the authors. Criticalizing moves beyond fixed static notions of "critical" scholarship toward a process of engaging in more fluid, expansive, and creative perspectives on the scholarship within work and organizational psychology. We illustrate how the set of papers within the Special Issue engages in such criticalizing of the field and offer new ways of thinking about and researching relevant topics in work and organizational psychology.